Clinical characteristics of patients with a family history of psoriasis: an observational epidemiological study in Chinese Han population - Cao, Lu; Lu, Lingyi; Yu, Yingzhe; Zhou, Huiying; Lin, Bingjiang (Frontiers in Medicine, 2024)
Introduction Psoriasis, a chronic inflammatory skin disease, is believed to be influenced by both genetic and environmental factors. Despite this understanding, the clinical epidemiological status of psoriasis patients with a family history of the disease remains uncertain. Methods In this study, we participated in a multicenter observational epidemiological study involved over 1,000 hospitals and enrolled a total of 5,927 psoriasis patients. These patients were categorized into two groups based on the presence or absence of a family history of psoriasis: family history cases (896) and sporadic cases (5,031). The clinical manifestations of these two groups were analyzed through clinical classification, comorbidities, treatment response, and other relevant factors. Results The findings of our study indicate that individuals with a family history of psoriasis predisposition exhibit a notably elevated prevalence of psoriatic arthritis compared to those with sporadic occurrences. Moreover, patients with a family history of psoriasis display a more rapid and efficacious response to secukinumab. Additionally, individuals with moderate to severe psoriasis are at a heightened risk of developing cardiovascular and liver diseases in comparison to those with mild psoriasis, with no discernible impact of familial history on the likelihood of comorbidities. Discussion Our study identified the clinical characteristics of individuals with a familial predisposition to psoriasis, offering novel insights into the management and therapeutic approaches for patients with this condition.